Carbon fractions as sensitive indicators of quality of soil organic matter - Westerhof, R; Vilela, Lourival; Ayarza, Miguel Angel; Zech, W. (International Center for Tropical Agriculture, 1999)
Soil organic matter quality is usually seen as a major attribute of soil quality. In this study, we extracted organic carbon with water (WEOC) or with potassium permanganate (PEOC). We assessed these extractions for their potential as sensitive indicators of the effect of land use on two important soil functions: biological activity and nutrient availability. Water-extractable organic carbon and PEOC were better correlated with C and N mineralization in the laboratory than were total and stable C, and were also more influenced by the mineralization flush that occurs at the beginning of the wet season. However, the more stable fraction also seemed to contribute to the pool of mineralizable C and N and was, within 5 years, significantly affected by changes in land use. Extraction of labile soil organic carbon with water and permanganate is an easy and valuable screening method for comparing the short-term effects of land-use systems on biological activity and nutrient availability in the soils of the Brazilian savannas.